PENGEMBANGAN MEDIA PEMBELAJARAN MULTIMEDIA INTERAKTIF MENGGUNAKAN ADOBE FLASH CS3 PADA MATAKULIAH MEDIA PEMBELAJARAN EKONOMI YANG MENERAPKAN METODE PROJECT BASED LEARNING - Ika Parma Dewi; Rani Sofya; Titi Sriwahyuni (Universitas Negeri Padang, 2018)
This study aims to produce, analyze validation tests, practicalities and effectiveness of interactive multimediaUsing Adobe Flash CS3 for Economics Learning Media Courses that Implement Project Based LearningMethods. This research uses research and development (R & D) methods. The module development model usesthe IDI (Instructional Development Institute) model, the principles of the system approach which include threestages, namely define, develop, and evaluate. This interactive multimedia in the form of learning media that hasbeen valid can help students to better understand and improve the subjects of economic learning media thatapply the Project Based Learning Method. Effectiveness Test of interactive multimedia economic learning mediacourses that use the project Based Learning method as a supporting media for independent learning states thatinteractive multimedia is effective, this is evidenced by the improvement in student learning outcomes.